Evaluation of the Utilization of Tax Incentive Policies during the Covid-19 Pandemic in the Framework of National Economic Recovery - Ratih Kumala; Ibrahim Abu Bakar (Yayasan Ilomata, 2022)
Until now, Indonesia still faces Covid-19 and is still in the process of economic recovery. However, the Directorate General of Taxes (DGT) was able to achieve the target of 100% tax revenue according to the target mandated in the 2021 State Budget even before the close of the year. At the end of 2021 tax incentives that have been utilized in the framework of the National Economic Recovery Program have reached IDR 63.16 trillion (100.5%) from the ceiling of IDR 62.83 trillion. This achievement is thanks to the contributions of all Taxpayers who continue to be committed to paying taxes. On this achievement, the government continues to show improvement efforts that must be maintained momentum, in order to continue to the 2022 state budget. The purpose of this study is to find out and analyze the evaluation of the utilization of tax incentive policies during the covid-19 pandemic in the framework of national economic recovery. This research uses descriptive qualitative methods through literature studies. In the evaluation of the utilization of tax incentive policies during the Covid-19 pandemic, it was explained that this tax revenue is one of the many state revenues that participate in supporting the nation and the country.